The development of consistency and flexibility in manual pointing during middle childhood. Issue 5 (21st May 2018) - Golenia, Laura; Schoemaker, Marina M.; Otten, Egbert; Tuitert, Inge; Bongers, Raoul M.
Abstract: Goal‐directed actions become truly functional and skilled when they are consistent yet flexible. In manual pointing, end‐effector consistency is characterized by the end position of the index fingertip, whereas flexibility in movement execution is captured by the use of abundant arm‐joint configurations not affecting the index finger end position. Because adults have been shown to exploit their system's flexibility in challenging conditions, we wondered whether during middle childhood children are already able to exploit motor flexibility when demanded by the situation. We had children aged 5–10 years and adults perform pointing movements in a nonchallenging and challenging condition. Results showed that end‐effector errors and flexibility in movement execution decreased with age. Importantly, only the 9‐10‐year‐olds and adults showed increased flexibility in the challenging condition. Thus, while consistency increases and flexibility decreases during mid‐childhood development, from the age of nine children appear able to employ more flexibility with increasing task demands.